Efektivitas Penerapan Aturan Laporan Harta Kekayaan dalam Menjamin Transparansi Harta Kekayaan Perangkat Daerah Pemerintah Kabupaten Sumba Timur - Charla Sinatra; Josef Mario Monteiro (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The problems in this study are: 1. How far is the effectiveness of the implementation of the East Sumba Regency Government's Regional Apparatus Asset Report rules?; and 2. What are the factors that hinder the effectiveness of the implementation of the East Sumba Regency Government's Regional Apparatus Asset Report rules? The purpose of this study is to determine and analyze the effectiveness of the application of the rules of the East Sumba Regency Government Regional Apparatus Asset Report. To determine and describe the factors that hinder the effectiveness of the application of the East Sumba Regency Government Regional Apparatus asset report rules. The type of research used by this researcher is empirical juridical method and the data is analyzed descriptively qualitative where the focus of the research is data collection of mandatory LHKPN, LHKPN Verification, and Legal Sanctions, as well as inhibiting factors, namely research whose data is directly obtained from the research location of 10 resource persons. The results of this study indicate that both the level of reporting and verification of LHKPN is not as expected, and the legal sanctions used are still considered weak. The inhibiting factors include legal factors that are considered less assertive related to LHKPN, less strict law enforcement against officials, inadequate facilities and infrastructure factors, and legal awareness factors of officials who are considered less responsible. It is recommended that state organizing officials immediately report their assets to the KPK and there is a need to improve regulations related to legal sanctions. Legal factors need to be improved in addition to the completeness of the rules and legal sanctions, law enforcement factors need strict action against Mandatory Reporters, facilities and infrastructure factors require the availability of adequate wifi facilities and provide competency training to employees related to the LHKPN filling process, as well as legal awareness factors to be more committed in carrying out their duties and responsibilities.